PROCEDURAL JUSTICE AND EMPLOYEES’ INTENTION TO LEAVE: THE MEDIATING ROLES OF JOB CHARACTERISTICS AND MEANINGFUL WORK IN THE POULTRY INDUSTRY - Steffiera Novenska; Barry, Rinto Rain (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
This study examines the effect of procedural justice on employees’ intention to leave, with job characteristics and meaningful work as mediating variables, in PT XYZ within the poultry industry. This industry plays a strategic role in supporting GDP and national food security, yet it continues to face high employee turnover. Data were collected from 200 permanent employees using a Likert-scale questionnaire (1–5) and analyzed using PLS-SEM. The results show that job characteristics significantly influence meaningful work and reduce intention to leave. Procedural justice also has a positive effect on job characteristics and meaningful work, while simultaneously lowering intention to leave. Moreover, meaningful work mediates the relationship between job characteristics and procedural justice on intention to leave, including a dual mediation pathway through job characteristics and meaningful work. These findings highlight the importance of implementing procedural fairness, managing job characteristics, and enhancing meaningful work as effective employee retention strategies. The study also provides practical insights for managers to strengthen employee satisfaction, engagement, and loyalty. Keywords: Procedural Justice, Job Characteristics, Meaningful Work, Intention to Leave